Laparoscopic orchiopexy of palpable undescended testes_ experience of a single tertiary institution with over 773 cases - Jia You; Gang Li; Haitao Chen; Jun Wang; Shuang Li (BMC, 2020)
Abstract Background Discuss the superiority of laparoscopic orchiopexy in the treatment of inguinal palpable undescended testes. Methods Inclusion criteria: Preoperative examination and color Doppler ultrasound examination confirmed that the testes were located in the inguinal canal and could not be pulled into the scrotum, except for retractive and ectopic testes. The surgical steps were depicted as follow. The retroperitoneal wall was carved by ultrasonic scalpels, separates the spermatic vessels closed to the inferior pole of the kidney if necessary, dissects the peritoneum of vas deferens, cuts the testicular gubernaculum, and pulls back the testicle into the abdominal cavity. Besides, protect the vas deferens, and descend the testes to the scrotum and fix them without tension. Results There were 773 patients with 869 inguinal undescended palpable testes, 218 cases on the left side, 459 cases on the right side and 96 cases with bilateral undescended testes, whose age ranged from 6 months to 8 years, with an average of 20 months. All testes were successfully operated, no converted to open surgery. The average operation time was (34.8 ± 5.4) min. There were 692 testes have an ipsilateral patent processus vaginalis (89.5%); In 677 cases of unilateral cryptorchidism, 233 cases (34.4%) have a contralateral patent processus vaginalis, and laparoscopic percutaneous extraperitoneal closure the hernia sac carry out during the surgery. There was no subcutaneous emphysema during the operation, no vomiting, no abdominal distension, no wound bleeding and obvious pain after surgery, especially wound infection is rarely. Doppler ultrasound was evaluated regularly after surgery. The patients were followed up for 6 to 18 months. All the testes were located in the scrotum without testicular retraction and atrophy. No inguinal hernia or hydrocele was found in follow-up examination. Conclusion Laparoscopic orchiopexy manage inguinal palpable cryptorchidism is safe and effective, and there are obvious minimally invasive advantages. Furthermore, It could discover a contralateral patent processus vaginalis, and treat at the same time, which avoid the occurrence of metachronous inguinal hernia.